2016
DOI: 10.1186/s13148-016-0282-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based DNA methylation as biomarker for breast cancer: a systematic review

Abstract: Multiple studies have investigated global DNA methylation profiles and gene-specific DNA methylation in blood-based DNA to develop powerful screening markers for cancer. This systematic review summarizes the current evidence on methylation studies that investigated methylation level of blood-derived DNA of breast cancer (BC) patients in comparison to healthy controls by conducting a systematic literature review in PubMed and Web of Science. Essential results, such as methylation levels of BC cases and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 78 publications
2
96
1
1
Order By: Relevance
“…Aberrant methylation patterns in tumor cells are associated with the development of BC 50,51 . Wong et al 52 demonstrated that the constitutional DNA methylation of the BRCA1 promoter was significantly associated with an increased risk of early-onset BC in women under the age of 40 years.…”
Section: Epigenetic Profile In Ywbcmentioning
confidence: 99%
“…Aberrant methylation patterns in tumor cells are associated with the development of BC 50,51 . Wong et al 52 demonstrated that the constitutional DNA methylation of the BRCA1 promoter was significantly associated with an increased risk of early-onset BC in women under the age of 40 years.…”
Section: Epigenetic Profile In Ywbcmentioning
confidence: 99%
“…Although the possibility that global DNA methylation reflects a novel breast cancer risk factor cannot be ruled out on the basis of these findings, a plausible implication of the observed lack of association between global WBC DNA methylation and most known or suspected breast cancer risk factors is that the association between global WBC DNA methylation and breast cancer, if it exists, is due to a disease effect [16, 59]. …”
Section: Discussionmentioning
confidence: 99%
“…Global hypomethylation contributes to cancer development and progression through activation of oncogenes (Van Tongelen, Loriot, & De Smet, ) and chromosomal instability (Gaudet et al, ). Changes in global CpG methylation can be monitored by measuring the methylation of repetitive elements in DNA (e.g., LINE‐1 and Alu) or the per cent of methylated DNA by luminometric methylation assay (LUMA), using mean methylation intensities of Infinium HumanMethylation 450 k probes (β‐value), or quantifying the concentration of 5‐methyldeoxycytosine (5‐mdC; Tang, Cheng, Cao, Surowy, & Burwinkel, ). Using the β‐value approach, a study reported an inverse association between BC incidence and global CpG methylation (OR = 0.42; 95% CI [0.20, 0.90]) in peripheral blood of BC patients ( n = 420; Severi et al, ).…”
Section: Dna Methylation Biomarkers Of Bcmentioning
confidence: 99%